Early life adversity and children's competence development: evidence from the Mannheim Study of Children at Risk - Friedhelm Pfeiffer; Dorothea Blomeyer; Katja Coneus; Manfred Laucht (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
This paper investigates the role of early life adversity and home resources in terms of competence formation and school achievement based on data from an epidemiological cohort study following 364 children from birth to adolescence. Results indicate that organic and psychosocial risks present in early life as well as the socio-emotional home environment are significant predictors for the formation of competencies. Competencies acquired at preschool age predict achievement at school age. A counterfactual analysis is performed to assess trade-offs in the timing of interventions in the early life cycle.
Keywords: I21; J13; I28; 330